Smart Classrooms at University: Innovation and ICT in Language Teaching - García Rodríguez, Joseph; Prat Sabater, Marta (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The use of smart classrooms improves the linguistic competence of university students. The objectives of this research are to clarify how these digital environments are constituted and to show the effectiveness of methodological advances with the purpose of promoting collaborative learning. The results are obtained from a survey aimed at different universities. The development of an e-portfolio is advocated as evidence of the teaching-learning process. The proposal is based on the socioconstructivist theory and the resolution of problems related to spelling. In short, smart classrooms must be created in universities and the integration of ICT in teaching must be improved.